Karakteristik Struktur, Amilograf, dan Kecernaan Pati Alami Jelai (Coix lacryma-jobi L) - Fiqtinovri, Siti masithah; Adriansyah, Didi; ., Risnafaty (Universitas Sebelas Maret (UNS), 2023)
Jelai (Coix lacryma jobi L.) that is cultivated in Bulungan Regency has thin and soft skin, yellowish brown in color and slightly shiny surface. The high content of starch and other components in barley increases the potential of Jelai as a food that has functional properties. This study aims to examine the relationship between the structural characteristics, amylograph properties, and digestion of Jelai natural starch (PAJ) and compare it with commercial cassava starch (PS) and corn starch (PJ). The research is started with the isolation process of jelai starch and then structural observations were carried out by SEM test, amylograph properties through RVA test, and digestibility including rapidly digestible starch (RDS), slowly digestible starch (SDS), and resistant starch (RS). PAJ has a low amylose content and a polygonal morphology with a clearly visible central pore / channel. The crystallinity of PAJ is slightly high with A-type crystalline, the same as PJ and PS. The starch structure in PAJ contributed to a slightly lower gelatinization temperature compared to PJ and the lowest setback viscosity compared to PJ and PS which indicated that PAJ was more resistant to retrogradation, as well as the highest RS levels and the lowest RDS compared to PJ and PS.